OBJECTIVE TESTS FOR THE EVALUATION OF COCHLEAR IMPLANT CANDIDATES - Mârţu Cristian; Sebastian Cozma; Luminiţa Rădulescu; Mârţu Dan (Romanian Society of Oral Rehabilitation, 2013)
Introduction: Cochlear implant indications have changed during the last decade. The objective tests are important in the cochlear implantation procedure. Purpose of the study: We proposed an evaluation for the objective tests in establishing a corect indication for cochlear implant in patients with bilateral sensorineural deafness. Materials and methods: We studied a group of 34 patients with bilateral sensorineural hearing loss tested by subjective and objective methods for an eventual cochlear implantation. Results: 74% of the patients presented a profound bilateral sensorineural hearing loss, 15% a severe type, 4% medium, 3% fluctuant and 4% cofosis. The examined patients fulfill the auditory criteria that justify the cochlear implant procedure. Discussions: The evaluation by subjective tests is followed by objective tests, offering provative evidence in clear cases and also in unclear ones. As a supplimentary measure, all the patients evaluated by subjective tests in establishing the possibility for cochlear implantations received at least one objective form of testing. Conclusions: Currently, the objective tests represent an important step in the reccomandation for cochlear implant. In all cases (excepting young children) the objective tests are compared/correlated with the subjective tests before the implantation procedure, specially with the subjective evaluation by a conventional prosthesis.